Centrifugal compressors of turboexpander units: development of approaches and experience of optimal design - Yu. B. Galerkin; A. F. Rekstin; V. B. Semenovskiy; L. N. Marenina; O. A. Solovyeva; A. A. Drozdov; L. N. Rozanov; P. N. Brodnev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The process of designing a new turboexpander unit using the Universal modeling method consists of several stages: preliminary design, optimization, calculation of gas dynamic characteristics. The development of modern computational methods and the accumulation of experimental research results has allowed to improve mathematical models in the field of calculation and design of CC turbo-expander units. The resulting model includes 22 empirical coefficients, the calculation error is 1,8 %, which is sufficient for its practical application in project activities.